Zinc plus cyclo-(His-Pro) promotes hippocampal neurogenesis in rats. (17th December 2016) - Choi, Bo Young; Kim, In Yeol; Kim, Jin Hee; Lee, Bo Eun; Lee, Song Hee; Kho, A Ra; Sohn, Min; Suh, Sang Won
Highlights: Vesicular zinc was increased in the mossy fiber area after zinc plus cyclo-(His-Pro) (ZC) treatment. The number of neural progenitor cells and immature neurons were increased in the hippocampus after ZC treatment. The present study demonstrates the essential role of zinc in modulating hippocampal neurogenesis. Abstract: Zinc is a central actor in regulating stem cell proliferation and neurogenesis in the adult brain. High levels of vesicular zinc are found in the presynaptic terminals. It has been demonstrated that high levels of vesicular zinc are localized in the presynaptic terminals of the granule cells of the dentate gyrus (DG) and that neurogenesis occurs in the subgranular zone (SGZ). Furthermore, zinc chelation reduces hippocampal neurogenesis in pathological conditions such as hypoglycemia, epilepsy and traumatic brain injury. Here we test the effects of zinc plus cyclo-(His-Pro) (CHP) treatment on neurogenesis in the adult SGZ. In order to increase brain zinc, Sprague–Dawley (SD) rats, aged 5 weeks, were given zinc plus CHP (ZC, 27 mg/kg) orally available once per day for 2 weeks. BrdU was intraperitoneally injected 2 times per day for 4 consecutive days starting 1 week after initial ZC treatment. Neurogenesis was analyzed by BrdU, Ki67 and doublecortin (DCX) immunostaining. The number of progenitor cells and immature neurons were significantly increased in the DG following 2 weeks of ZC treatment. Hippocampal vesicular zinc content was evaluated with TSQ staining. Vesicular TSQ fluorescent intensity was seen to increase in the mossy fiber area at 2 weeks after ZC treatment. The present study demonstrates that zinc supplementation by ZC treatment increases hippocampal neurogenesis and levels of vesicular zinc. These findings provide evidence in support of the essential role of zinc in modulating hippocampal neurogenesis.